The background of students' performance - Nagy-Kondor, Rita (Teaching Mathematics and Computer Science, 2006)
The question to which we were seeking was: how can we reveal the students' strategies and mental process by following their work precisely and by finding out what correlation these have with their efficiency. Our aim was to understand the factors behind of students' achievement. We tried to follow up the process of problem solving by looking at the number of wrong turnings.